Trends in age dynamics of the use parent-child conflict resolution tactics in Chinese families - Zhao Silu,; Fourmanov, Igor A. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
Trends in the age dynamics of tactics for resolving parent-child conflict in Chinese families are discussed. It was found that in different age periods (childhood and early adulthood), regardless of the sexes of the child and the parent, the most common tactics for resolving parent-child conflict are discipline, corporal punishment and psychological aggression. Mothers differ from fathers by their greater involvement in resolving parent-child conflicts with both girls and boys, especially during childhood. The frequency of parents’ use of tactics for resolving parent-child conflict tends to decrease as children grow up.
Keywords: discipline; disciplining; psychological aggression; physical punishment; violent behaviour; tendencies; tactics to resolve parent-child conflict